2007
DOI: 10.1111/j.1524-4725.2007.33280.x
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Biologic Effects, Clinical Efficacy, and Safety of Silicone Elastomer Sheeting for Hypertrophic and Keloid Scar Treatment and Management

Abstract: Silicone elastomer sheeting is a medical device used to prevent the development of and improve the appearance and feel of hypertrophic and keloid scars. The precise mechanism of action of silicone elastomer sheeting has not been defined, but clinical trials report that this device is safe and effective for the treatment and prevention of hypertrophic and keloid scars if worn over the scar for 12 to 24 hours per day for at least 2 to 3 months. Some of the silicone elastomer sheeting products currently on the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
99
1
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(109 citation statements)
references
References 90 publications
(266 reference statements)
3
99
1
6
Order By: Relevance
“…Silicone dressings in the form of plasters or gel are used in the treatment of hypertrophic scars and keloids [20,21]. The use of silicone dressings is recommended as a safe, non-invasive, simple, and effective method of prophylaxis [18,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Silicone dressings in the form of plasters or gel are used in the treatment of hypertrophic scars and keloids [20,21]. The use of silicone dressings is recommended as a safe, non-invasive, simple, and effective method of prophylaxis [18,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Various mechanisms have been proposed as possible modes of action for silicone-based agents and corticosteroids in the wound healing processes including: 1) an increased temperature or oxygen tension increasing collagenase activity and leading to collagen breakdown shrinking the scars [3,7], 2) occlusion and hydration of wounds [7,13]; reduction in transepidermal water loss decreases stimulation of keratinocytes which stops cytokine production [13], and 3) polarization of the scar tissue caused by a negative static charge between silicone and skin [14] and the modulation of growth factors [9,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested topical silicone gel to be the first-line option for prevention of HS and keloids [7,[15][16][17]. In the study by Chan et al [7] of 50 patients, sternal wounds were divided into two halves; one half was treated with silicone gel and the other half with placebo gel for 3 mon- ths.…”
Section: Discussionmentioning
confidence: 99%
“…Besides cosmetic complaints, others include pain, numbness and itching. [3][4][5] These nodular skin lesions may appear like neoplasms and capable of causing much physical disfigurement that borders on the patient's cosmetic and psychological trauma 6 . Whereas keloids grow beyond the original borders of the wound, hypertrophic scars do not extend beyond the original borders of the wound or injury 7 as shown in figures 1& 2.…”
Section: Introductionmentioning
confidence: 99%